(untitled) (TAMADDUN NURI JURNALI, 2024)
This article provides information about manuscript copies of the work "Qisasi Rabguzi" preserved around the world and manuscript copies available in the fund of the Institute of Oriental Studies of the UzFA, and some of them are classified given